2019
DOI: 10.14814/phy2.14175
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of maximum tongue protrusion force (MTPF) in healthy young adults

Abstract: We propose that tongue protrusive strength and tone may be related to upper airway patency, and when protrusive strength is reduced, individuals are at higher risk of developing sleep apnea, or speech/swallow disorders. The goal of the current study was to determine normative values of maximum tongue protrusion force (MTPF) in healthy young adults, using a unique newly developed device. We hypothesized that MTPF would be greater in males than in females. One hundred and one healthy young adults (mean age: 22.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Tongue force is dependent on the status of the tongue muscles. 11 Therefore, considering the observations of the present study, further extensive research into the effect of the OSMF disease process on the lingual muscles is very much required.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Tongue force is dependent on the status of the tongue muscles. 11 Therefore, considering the observations of the present study, further extensive research into the effect of the OSMF disease process on the lingual muscles is very much required.…”
Section: Discussionmentioning
confidence: 93%
“…Kim et al measured protrusive force with the help of a piston device, whereas Rodrguez-Alcalá et al used a Tongue Digital Spoon to measure the tongue strength of 20 healthy subjects. 11 , 13 These studies compared the tongue force in both genders and also in young and elderly groups.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Biting force results indicated that neither the SSW nor fabricated PEEK specimens reached the maximum force of the estimated occlusal force at the incisal region (250 N). 24 , 25 , 26 Serious mechanical deformation can occur when the force directly acts on the lingual fixed retainer. Patients should also be warned to be careful when biting with the anterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum Von Mises stresses that occurred at the area of forces applied were recorded for comparison. All models were initially subjected to anteroposterior bending (10, 15, and 20 N) 23 , 24 to simulate lip and lingual forces, and any models with unacceptable Von Mises stresses were eliminated ( Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our development of the TDS technique was based on the study by Kim et al [ 15 ]. In that study, to measure the maximal isometric tongue protrusion force participants sat upright with the tongue extended 0.5–1 cm beyond the teeth to touch a piston.…”
Section: Discussionmentioning
confidence: 99%